Apigenin in cancer prevention and therapy: A systematic review and meta-analysis of animal models. (August 2022) - Singh, Deepti; Gupta, Meenakshi; Sarwat, Maryam; Siddique, Hifzur R.
Abstract: Background: Apigenin is being increasingly recognized as a cancer chemopreventive agent . We aimed to investigate the anticancer effects of Apigenin in in-vivo studies to know its present research status and how close or how far it is from the clinics. Methods: Several electronic databases such as PubMed, Springer, Cochrane, and ctri.gov.in were searched to fetch the relevant articles. We focused only on published animal studies that reported the anticancer effects of Apigenin against various cancers. Two reviewers independently assessed the risk of bias for each analysis, and the conflicting views were resolved later by consensus. Results: A total of 25 studies focused on the anticancer effects of Apigenin on various cancer types, including liver, prostate, pancreatic, lung, nasopharyngeal, skin, colon, colorectal, colitis-associated carcinoma, head and neck squamous cell carcinoma, leukemia, renal cell carcinoma, Ehrlich ascites carcinoma, and breast cancer were included. Overall, Apigenin reduces tumor volume (SMD=−3.597, 95% CI: −4.502 to −2.691, p < 0.001), tumor-weight (SMD=−2.213, 95% CI: −2.897 to −1.529, p < 0.001), tumor number (SMD=−1.081, 95% CI: −1.599 to −0.563, p < 0.001) and tumor load (SMD=−1.556, 95% CI: −2.336 to −0.776, p < 0.001). Further, it has no significant effect on the animal's body-weight (SMD=−0.345, 95% CI: −0.832 to 0.143, p = 0.165). Apigenin exerts anti-tumor effects mainly by inducing apoptosis/cell-cycle arrest. Conclusions: Our analysis suggests that Apigenin has potential anticancer effects against various cancers. However, the poor symmetry of the funnel plot suggested publication bias. Thus, it warrants further research to evaluate the potential of Apigenin alone or as an adjuvant for cancer treatment. Highlights: Apigenin possesses several beneficial properties, including anti-cancer. It has anti-cancer effects, especially in Hepatocellular carcinoma, Prostate, and Lung cancer. It had no significant effect on animals' body weight, suggesting its safe to use. Apigenin can be a promising anti-cancer agent alone or an adjuvant with approved drugs. Future studies are needed to enable its translation from bench to clinics.